2021
DOI: 10.3389/fcimb.2021.773410
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Sirtuin TcSir2rp3 Affects TcSODA Activity and Oxidative Stress Response in Trypanosoma cruzi

Abstract: Trypanosoma cruzi faces a variety of environmental scenarios during its life cycle, which include changes in the redox environment that requires a fine regulation of a complex antioxidant arsenal of enzymes. Reversible posttranslational modifications, as lysine acetylation, are a fast and economical way for cells to react to environmental conditions. Recently, we found that the main antioxidant enzymes, including the mitochondrial superoxide dismutase A (TcSODA) are acetylated in T. cruzi, suggesting that prot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…Previous studies have demonstrated that lysine acetylation regulates SODA activity in human and T. cruzi enzymes. Specifically, acetylation of K68 and K97 negatively affects enzyme activity in these organisms, respectively [26, 27]. To investigate whether this regulatory mechanism is conserved throughout evolution, we analyzed SODAs from A. fumigatus , D. melanogaster , D. rerio , T. cruzi , T. brucei , A. thaliana , and H. sapiens .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have demonstrated that lysine acetylation regulates SODA activity in human and T. cruzi enzymes. Specifically, acetylation of K68 and K97 negatively affects enzyme activity in these organisms, respectively [26, 27]. To investigate whether this regulatory mechanism is conserved throughout evolution, we analyzed SODAs from A. fumigatus , D. melanogaster , D. rerio , T. cruzi , T. brucei , A. thaliana , and H. sapiens .…”
Section: Resultsmentioning
confidence: 99%
“…Notably, all SODAs possess a conserved “funnel” region that plays a crucial role in directing the substrate towards the enzyme’s active site. This region is typically enriched with positively charged lysine residues, creating a pathway for negatively charged superoxide to reach the catalytic site [26, 27]. Consequently, acetylation of any lysine residue within this region could alter substrate direction due to the neutralization of positive charges [26, 27].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…sponse and other key cellular processes. (48,49,60,61,62) Lysine acetyltransferases (KATs) are responsible for transferring the acetyl group from acetyl-CoA to the lysine residues, while the lysine deacetylases (KDACs) remove the acetyl groups. (63,64) Moreover, bromodomain-containing proteins (BRDs) bind acetylated lysines and recruit proteins that will perform downstream regulatory functions.…”
Section: Drug Target Validation and The Prospection Of New Antileishm...mentioning
confidence: 99%